Jan Sarvaes, Thomas L. Jacobson and Shirley A. White (eds). Participatory Communication for Social Change. New Delhi: Sage Publications. 1996. 286 pages. Hardbound. Indian Rs 325.00. (The Pakistan Development Review, 1996)
Changing needs and aspirations of society is the fundamental element of the development process. The state’s failure to cope with this galvanises people to make collective decisions. In development projects, participation is very important to decision-making, as it involves the sharing of information, knowledge, commitment, and the right attitude. Participation, like sustainable development, has become one of those catchwords whose message is advocated by everyone, but with their own definition. In development, it is broadly understood as the active involvement of people in making decisions about the implementation of processes, programmes, and projects which affect them. It involves the equitable distribution of political and economic powers between different groups in a society, leading often to a decrease in the advantages of the élites. However, the term covers a wide variety of activities.